Why Public Service Matters - Durant, R. author. aut Link
XIV, 290 p. 10 illus.
Keywords: Why Public Service Matters conveys the importance, purpose, and nobility of a career as a civil servant in the United States. It does so, however, with an unflinching eye on the realpolitik that drives public administration in America's "compensatory state" and on the pitfalls of reformers' focus on bureaucratic, rather than democratic, administration. The book links the nation's ability to handle contemporary policy problems with the strategic, tactical, and normative quality of public management. In doing so, it offers newcomers a rare, concise, and accessible overview of the field. Readers will gain an appreciation for the challenges, choices, and opportunities facing public managers as they help advance a sense of common purpose informed by democratic constitutional values in twenty-first century America.